2021
DOI: 10.1016/j.ebiom.2021.103318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical biomarkers and associations with healthspan and lifespan: Evidence from observational and genetic data

Abstract: Background Biomarker-disease relationships are extensively investigated. However, associations between common clinical biomarkers and healthspan, the disease-free lifespan, are largely unknown. We aimed to explore the predictive values of ten biomarkers on healthspan and lifespan, and to identify putative causal mechanisms. Methods Using data from 12,098 Swedish individuals aged 47–94 years, we examined both serum concentrations and genetically predicted levels of ten g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As disease pathogenesis is often associated with underlying aging characteristics, common clinical serum biomarkers have the potential to assess longevity and healthy aging [ 2 , 3 ]. A test of 12,098 individuals aged 47–94 years indicated that glycemic, lipid, and inflammatory factors were significantly correlated with risks of chronic diseases and death, and biomarkers were predictive of health state and lifespan [ 4 ]. Blood biochemical indices and inflammatory markers were closely associated with disease production and progression.…”
Section: Introductionmentioning
confidence: 99%
“…As disease pathogenesis is often associated with underlying aging characteristics, common clinical serum biomarkers have the potential to assess longevity and healthy aging [ 2 , 3 ]. A test of 12,098 individuals aged 47–94 years indicated that glycemic, lipid, and inflammatory factors were significantly correlated with risks of chronic diseases and death, and biomarkers were predictive of health state and lifespan [ 4 ]. Blood biochemical indices and inflammatory markers were closely associated with disease production and progression.…”
Section: Introductionmentioning
confidence: 99%
“…These include HbA1c, fasting blood glucose, C-reactive protein, triglycerides, high-density lipoprotein cholesterol, ApoA1, and total cholesterol (X. Li et al, 2021). Ultimately, the utility of BA being reduced without a concomitant functional improvement and/or a decreased risk of mortality is questionable.…”
Section: Outstanding Questions and Limitations In The Fieldmentioning
confidence: 99%
“…In addition to estimating BA, it would be helpful to measure classical clinical biomarkers that are known to associate with lifespan and healthspan. These include HbA1c, fasting blood glucose, C‐reactive protein, triglycerides, high‐density lipoprotein cholesterol, ApoA1, and total cholesterol (X. Li et al, 2021). Ultimately, the utility of BA being reduced without a concomitant functional improvement and/or a decreased risk of mortality is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of EBioMedicine, Li and colleagues [4] studied the predictive value of commonly used clinical biomarkers of ageing using healthspan and lifespan as outcomes. To this end, they used a large and relatively healthy Swedish cohort for which extensive long-term longitudinal follow-up data on disease diagnosis and mortality was available.…”
mentioning
confidence: 99%
“…Some of the identified omics-based biomarkers have already shown to be better predictors of lifespan than the well-established clinical biomarkers of ageing, especially at higher ages [8À10]. Hence, it will be interesting to apply the methodological framework described in this proof-of-principle study by Li and colleagues [4] to determine the predictive value of these omics-based biomarkers on healthspan (and lifespan). The best (independent) omics-based biomarkers of ageing can subsequently be developed further so they can be incorporated in ongoing clinical studies to amend or replace the commonly used clinical biomarkers with the goal to identify and treat vulnerable individuals before the occurrence of (multi)morbidity.…”
mentioning
confidence: 99%